Teaching Political Science Research Methods in Hungary: Transferring Student-Centred Teaching Practices into a Subject-Focused Academic Culture - simon, eszter (European political science, 2014)
This article discusses the challenges of moving towards student-centredness in East-Central Europe through the example of Hungary’s subject-focused academic culture and the (re-)design of a political science research methods course at the University of Szeged for Spring 2012. Although countries participating in the Bologna Process undersigned the importance of student-centredness, few countries have actually yet moved in this direction. In addition, we know very little about how these instructional methods work outside the Western democratic context. I show that research into teaching is an important means to improve the process of education and that there are specific problems in transferring student-centredness into post-Communist higher education settings. Finally, I argue that knowing one’s teaching context is vital for planning student-centred courses effectively, which would be greatly fostered by experiencing other teaching contexts through early-career teacher exchanges. The European Commission has recently affirmed its commitment to staff exchanges, but such opportunities are only likely to be beneficial if they go beyond the current 6-week long exchange scheme that the Erasmus programme offers.